BRIDGING THEORY AND PRACTICE: TVET ACTIVITIES FOSTERING KNOWLEDGE APLLICATION IN STEM - Suhaizal Hashim,; Mohd Erfy Ismail,; Khairul Anuar Abdul Rahman, (2026)
The purpose of this book is to provide educators, students, and parents with guidance on the role of Technical and Vocational Education (TVET) in STEM (Science, Technology, Engineering, And Mathematics) education. Specifically, it addresses how to implement current trends in the classroom, particularly when it comes to TVET-STEM activities in Malaysia. This paper aims to give an overview of TVET’s role in STEM education, which is to help people discover and develop their educational potential, career, and psychology in order to reach an optimal level of social motivation and personal development. This is in accordance with the needs of 21st-century education and the realization that many educators, parents, and students are still unsure about this role. The progress of STEM education is greatly aided by TVET. Generally speaking, TVET allows students to apply STEM concepts in real-world contexts through experiential learning. This aids in their integration of STEM concepts with practical, industrial uses. Furthermore, TVET offers a different kind of education for people who cannot or will not pursue postsecondary education in STEM fields. This enables people to get practical skills in a range of STEM fields, including as mechanical, electrical, and information technology, without needing to pursue an extensive academic degree.